2018
DOI: 10.1080/24750573.2017.1422958
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of psychiatric disorders in children refugees in Turkey’s Yazidi refugee camp

Abstract: Objective: To examine the mental health states of a sample of Yazidi refugee children and adolescents who migrated from war-torn Iraq's Sinjar region and to determine the risk and protective factors for psychiatric disorders among the refugee children and adolescents. Method: The participants of this research were children and adolescents between ages 6 and 17 who live in a refugee camp in Turkey. Their parents/guardians provided written informed consents for the research. The research was approved by the Ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 45 publications
1
46
0
2
Order By: Relevance
“…PTSD symptom severity was also associated with the nature of the event that caused the injury. It has been shown that intense PTSD symptoms develop in approximately half of all traffic accidents and burn patients and that the severity of PTSD symptoms in these children may be as severe as in refugees (35,36) or earthquake victims (32). Considering that PTSD can affect children's social and biological development and academic life which lasts for many years (18,37,38), it is understood that focusing on only the physical damage of accident and injuries means leaving the patient at a serious risk of mental problems.…”
Section: Discussionmentioning
confidence: 99%
“…PTSD symptom severity was also associated with the nature of the event that caused the injury. It has been shown that intense PTSD symptoms develop in approximately half of all traffic accidents and burn patients and that the severity of PTSD symptoms in these children may be as severe as in refugees (35,36) or earthquake victims (32). Considering that PTSD can affect children's social and biological development and academic life which lasts for many years (18,37,38), it is understood that focusing on only the physical damage of accident and injuries means leaving the patient at a serious risk of mental problems.…”
Section: Discussionmentioning
confidence: 99%
“…Of the participants, 57.5% were male, 25 Table 1 shows the comparison of mean CPTS-RI, CDI, and STAIC-T scores according to socio-demographic characteristics of the children.…”
Section: Resultsmentioning
confidence: 99%
“…It was found in the studies conducted with Syrian refugee children in Turkey that children witnessed the death or injury of one of their parents, death of a friend, or they themselves suffered ignorance or abuse. In addition, the children whose houses were destroyed and had to migrate to Turkey experienced higher levels of posttraumatic stress disorder, anxiety, depression, behavioral, and sleep disorders . Studies conducted with the children exposed to the war in Uganda revealed that the depression, anxiety, and posttraumatic stress disorder scores of the children who experienced war‐related events and lost their parents were higher .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations